Records Management Policy in Enhancing Governance in Homa Bay County Headquarters, Kenya - Obunde, Joan Atieno; Wasike, Jotham; Awuor, Mzee (University of Dar es Salaam Library Journal, 2022)
Globally, records management plays major role in enhancing governance. The study objective was to examine the role of records management policy in enhancing governance at Homa Bay (HB) County Headquarters, Kenya. Target population comprised of 306 employees who are the custodians of records within the County Headquarters. Stratified technique was used to classify employees into strata. Yamane simplified formula was used to obtain a sample size of 174 respondents, which was proportionately distributed per department using random sampling technique. Structured questionnaires and interview schedules were pretested to determine validity and reliability and thereafter employed to collect data. Quantitative data was analyzed using descriptive statistics with the aid of IBM €“ SPSS (Version 23), presented in a table and interpreted in mean, frequencies, percentages, and standard deviation. Qualitative data was analysed using content analysis. The finding showed that records management policy was available in HB, though some employees were unaware. The study concluded that records managers in HB County should instill awareness among staff on the importance of records management policy. Based on the finding and conclusion, the study recommends, firstly, that HB records managers should ensure records management policy is properly documented and shared with all employees managing records with a view of increasing efficiency in the information flow thus enhancing governance and secondly, HB would identify areas of weakness in records management policy and focus on improvement.